Gen z's activities and needs for urban recreational parks - Ghani, Nurfaezah; Mansor, Mazlina; Zakariya, Khalilah (Malaysian Institute of Planners, 2018)
A public recreational park for youth is important in promoting leisure activities for their health. Engagement with outdoor activity contributes to healthy growth development physically, mentally and socially. Youth prefers places that offer favourable facilities where they can express themselves with presence friends. The study focuses on Generation Z youth (Gen Z), who are born between the mid of the 1990s through the late 2000s. The study investigates Gen Z activities and needs of recreational parks in Kuala Lumpur. The study obtained 564 respondents who lived in five strategic zones in Kuala Lumpur. Their responses were statistically analyzed using the SPSS. Results showed that the Gen Z frequented recreational parks near their homes. Titiwangsa Lake Garden, KLCC Park and Kepong Metropolitan Park are among their place preference. A recreational park for them should have more natural attributes and meet their active lifestyle. The places encourage them to have an active engagement and positive socialization with others.